2008
DOI: 10.1103/physreva.78.022322
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the dynamics of entanglement: Sudden death, complementarity, and continuous monitoring of the environment

Abstract: We report on an experimental investigation of the dynamics of entanglement between a single qubit and its environment, as well as for pairs of qubits interacting independently with individual environments, using photons obtained from parametric down-conversion. The qubits are encoded in the polarizations of single photons, while the interaction with the environment is implemented by coupling the polarization of each photon with its momentum. A convenient Sagnac interferometer allows for the implementation of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
191
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(195 citation statements)
references
References 81 publications
2
191
0
2
Order By: Relevance
“…There are at most d 2 independent Kraus operators, where d is the dimension of the system [31,32]. Together with Eq.…”
Section: Open System Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are at most d 2 independent Kraus operators, where d is the dimension of the system [31,32]. Together with Eq.…”
Section: Open System Dynamicsmentioning
confidence: 99%
“…Together with Eq. (5), the dynamical evolution of the complete system-environment state can be also given by the following map [31] :…”
Section: Open System Dynamicsmentioning
confidence: 99%
“…Sibasish Ghosh showed that it is not possible to discriminate between any three Bell states if only a single copy is provided and if only local operations and classical communication are allowed [14]. At present most of the studies consider only one of the Bell states but ignore the other three [9][10][11][12][13]15,16] because different Bell states will give the same result without considering environment. On the other hand, Philip Walther and Anton Zeilinger realized a probabilistic for Bell state analyzer for two photonic quantum bits by use of a non-destructive controlled-NOT gate based on entirely linear optical elements [17].…”
Section: Introductionmentioning
confidence: 99%
“…A reasonable model is considered as one open qubit S entangled with an ancillary qubit A which is isolated from a local vacuum reservoir E [34]. The decoherence process can also be obtained by the map in terms of the total system-environment state [35,36]. The evolution of the states for the total system can be obtained by…”
Section: Dynamics Of Quantum Entanglementmentioning
confidence: 99%